(untitled) (Research, Society and Development, 2025)
The general objective of this study is to promote educational actions among the academic community and the local population regarding the risks of self-medication and the proper disposal of medicines, encouraging safe and sustainable practices for public health and environmental preservation. This study is a social, qualitative and quantitative research designed as an experience report. The campaign collected expired or near-expired tablets from drugstores, a hospital pharmacy and local residents. The data showed a significant accumulation of medications used to treat chronic diseases. The educational actions helped clarify the risks of self-medication and the environmental impacts of improper disposal in household waste. Part of the valid medications was donated to a local health institution that supports people in vulnerable situations. The initiative brought students, professionals and the community closer together, strengthening practices of care, social responsibility and environmental protection.